Tantangan Dalam Pengembangan Community Based Tourism di Desa Wisata Denai Lama Berbasis Analisis SWOT - Muhammad Khadry; Riana Handayani Silalahi (Journal of Economic Education and Entrepreneurship Studies, 2024)
Tourism Village is a program used to explore the potential of villages that are managed as tourist attractions. Local communities in the community-based tourism concept have the awareness to actively participate in tourism development in their region through cultural, social and environmental sustainability. The keywords attached to the concept of community-based tourism are community empowerment and community participation. The aim of this research is to identify challenges in developing Community Based Tourism in the Denai Lama tourist village, Pantai Labu, Deli Serdang, North Sumatra. The method used in this research is descriptive with a qualitative approach using SWOT analysis to determine the strengths, weaknesses, threats and opportunities that exist in the Denai Lama Tourism Village. The type of data used is primary data through interviews with sources and secondary data obtained indirectly. Denai Lama Village or better known as Kampoeng Lama Tourism Village is one of the villages that is considered to have a lot of potential for development. The Kampoeng Lama tourist village has 3 tourist spots, namely Sanggar Circle, Paloh Naga Agrotourism, and Kamu Kawan Lama Market. The first challenge in developing community-based tourism is to unite community perceptions so that people are aware of tourism, understand and actualize Sapta Pesona. Then tourism training for the community has not been maximized in the field of digital marketing because human resources in this field still do not have the capacity to promote tourism.